Investigation of thermophysical properties of heat-insulating barrier manufactured by incremental rapid prototyping method - Paweł Gil; Maria Tychanicz (Advances in Mechanical and Materials Engineering, 2018)
This paper presents the results of experimental investigation of thermophysical properties of material manufactured with 3D printing technology with the use of fused deposition modelling (FDM) method. Cylindrically shaped samples with a diameter of 50.8 mm and with various fill density (from 10 to 100%) were prepared. The investigated material was PLA (polylactic acid, polylactide). The investigation was carried out in order to determine the density, thermal conductivity, thermal diffusivity and specific heat of tested material. The main aim of this paper was to determine the influence of fill density on thermal conductivity. The results can be useful in designing thermal insulation manufactured with rapid prototyping methods, operating in relative low temperature conditions (< 100°C).